LEVELS OF TUMOR NECROSIS FACTOR ALPHA AND INTERLEUKIN-17 IN FERTILE AND INFERTILE WOMEN WITH ENDOMETRIOSIS (Iraqi Journal of Medical Sciences, 2017)
Background: Endometriosis is described by the existence of endometrial tissue outside the uterine cavity. Infertility is one of clinical manifestation of endometriosis shown by the difference of fecundity.Objective: To compare the serum levels of TNF-? and IL-17 in fertile and infertile endometriosis patients.Methods: This study was conducted on 55 women patients with endometriosis (30 infertile women and 25 fertile women) and twenty apparently healthy controls. The technique used to reveal serum level of TNF-? and IL-17 was Enzyme-linked immune sorbent assay (ELISA).Results: This study revealed significant increase (p0.05) between controls and each group of patients. Moreover, there were significant increase (p0.05) between fertile patients and controls.Conclusion: The current results indicate that TNF-? and IL-17 might play a crucial role in endometriosis-related infertility.Keywords: Endometriosis, TNF-?, IL-17.Citation: Vean S.A. Al-Azawy. Levels of tumor necrosis factor alpha and interleukin-17 in fertile and infertile women with endometriosis. Iraqi JMS. 2017; Vol. 15(2): 159-164 . doi: 10.22578/IJMS.15.2.8
Keywords: Endometriosis; TNF; IL17